Guest

Please solve the question in the attachment.............

Please solve the question in the attachment.............

Question Image
Grade:12th pass

1 Answers

Aditya Gupta
2081 Points
4 years ago
this is quite an easy ques and can be done by assuming the polynomial as p(x)
then the given eqn becomes
 
d/dx(e^x*p(x))=x^n*e^x
or e^x(p(x)+p’(x))=x^n*e^x
or p(x)+p’(x)=x^n
obviously it is easy to find find p’(x) as it is a polynomial. now you can compare the coefficients of x^r on both sides of the eqn so as to form a recurrence relation from which ar is easily deduced.
in fact ar/ar-1 = n+1 – r, which is precisely true for ar= nPr (permutations)
but nPr= n!/(n – r)!
hence, ar= nPr= n!/(n – r)!

Think You Can Provide A Better Answer ?